Pierwsza polska „Antropologia” i jej autor Józef Jasiński - Gronkiewicz, Stanisław (Polskie Towarzystwo Antropologiczne, 1987)
Over half a century before the creation of the first anthropological institutions in Poland, a work was published in Poland being a testimony of the anthropological knowledge of Polish natural scientists from the turn of the 18th century.
The first Polish “anthropology” and its author Józef Jasiński